PENGARUH ARUS KAS BEBAS, KUALITAS AUDIT, KEBERADAAN EKSEKUTIF WANITA, DAN DIVERSIFIKASI USAHA TERHADAP MANAJEMEN LABA - Nur’aini Nur’aini; Darsono Darsono (Diponegoro Journal of Accounting, 2017)
This study aims to examine factors affecting earnings management practices such as the effect of free cash flow, audit quality, female executive presence, business diversification. The sample used in this study is a manufacturing company listed on the Indonesia Stock Exchange (IDX) period 2012-2015. The sampling method used in this research is purposive sampling and samples obtained as many as 387 samples. This study uses multiple regression analysis for hypothesis testing. The results of this study show that the variable of surplus-free cash flow and business diversification had a significant positive effect on earnings management which is measured using discretionary accrual while audit quality variable has significant positive influence and the female executive existence variable has positive non-significant influence to earnings management.